211k views
1 vote
Please answer soon for 14 points

Please answer soon for 14 points-example-1
User Smokku
by
4.8k points

1 Answer

3 votes

Answer:

B

Explanation:

If the function given is SQUARED, the expression would be:


(5(2^x))^2

We can use the rule below to further simplify:


(ab)^c=a^c*b^c

We have:


(5(2^x))^2\\=(5)^2 * (2^x)^2

We can use another exponential rule to simplify this. Shown below:


(a^b)^c=a^(b*c)

Thus, we have:


(5)^2 * (2^x)^2\\=25*2^(2x)\\=25(2^(2x))

Correct answer is B

User Fawaz
by
5.6k points